As condições de trabalho no pós-ocupação da moradia pelo programa minha casa minha vida: um estudo de caso da população do condomínio Flor de Jasmim no Município de Osasco - SP - Borges, Sabrina Dantas Barretto Soares (2016)
The purpose of this paper is analyzing the impact of labor relations during the afteroccupation phase of housing by the Program “Minha Casa Minha Vida”- PMCMV, through a case study of the population from Jasmine Flower Condominium located in Osasco, a city in the Metropolitan area of the city of São Paulo in the State of São Paulo. It starts by presenting the PMCMV, its regulations and normative conduct, its implementation and challenges faced during it, which is analyzed throughout the discussion about Social Housing policy and permeated by the presentation and analysis of the Osasco space-social scenario and the profile of the population attended by the MCMV program. The methodology used to analyze the population of the Jasmine Flower Condominium was the same originally created by the group of researchers from the Project “Evaluation of the social work and impact in the families’ life at MCMV: Municipality Osasco/ SP”, within Núcleo de Estudos e Pesquisas sobre Movimentos Sociais - NEMOS (Nucleus of Studies and Research on Social Movements), from the Program of Postgraduate Studies in Social Service and from the Coordenadoria de Estudos e Desenvolvimento de Projetos Especiais - CEDEPE (Coordination of Studies and Development of Special Projects) and from Pontifícia Universidade Católica de São Paulo - PUC-SP (Catholic University of São Paulo), whose evaluation instruments and indicators have been organized into four axis: socioeconomic conditions and insertion in the working world; the right to the city and to urban insertion; participation, sociability and social work; and, residents needs